Modernization and Development: A Historico-Contemporary Approach Through Justin Labinjoh's Narratives (2017)
Understanding development is a strategic issue in every human society. This is because central to humans is the need to develop, which is why societies over the ages have not only sought to develop, they have also attempted to understand what development is all about, how best to develop and what the outcomes of development should be. This is why scholars and nations have commonly categorized countries/societies as developed and developing/underdeveloped.Of interest however are continuous scholarly attempts at unravelling trends in development discourse. This article therefore engages the contributions of Justin Labinjoh, a foremost development thinker a scholar at the universtiy of lbadan until his death in 2001. Focusing on his unpublished manuscript 'Development: A History and Critique of an Idea ', the paper reviews how the history at Western Europe informed, and is still informing Sociology as a discipline, it’s dwories and, by extension, Sociology of Development which has been dominated by modernization theory